Combination of laser and photogrammetric techniques for precise modeling and measurement of human faces - Setan, Halim; Majid, Zulkepli; Chong, Albert; Ahmad, Anuar (2006)
Special medical applications such as craniofacial reconstruction require precise modeling and measurement of human faces. Many surgeons still use traditional contact method (e.g. calipers) for measuring anthropometric landmarks on human face. Our current multi-disciplinary research focuses on the development of surgical planning system for craniofacial reconstruction. The craniofacial reconstruction requires the following: imaging (non-contact, precise, rapid), 3D models (digital and physical), database, and surgical planner. This paper discusses our research works on the development of the imaging system (close range, non-contact, and real time) and measurement/3D modeling for craniofacial. The developed imaging system combines the laser scanning and photogrammetric techniques for acquiring high-resolution 3D models (and precise measurement) of craniofacial soft tissue. The results show that measurements to mm- level precision are achievable, indicating the suitability of the approach for practical craniofacial applications.